Are breast cancer patients with low distress at diagnosis at risk of psychological symptoms later in their disease trajectory? Considerations for when to screen for distress - Rikke Langballe; Birgitte Mertz; Niels Kroman; Thomas Maltesen; Susanne Rosthøj; Pernille Envold Bidstrup (Acta Oncologica)
Introduction: To target psychological support to cancer patients most in need of support, screening for psychological distress has been advocated and, in some settings, also implemented. Still, no prior studies have examined the appropriate ‘dosage’ and whether screening for distress before cancer treatment may be sufficient or if further screenings during treatment are necessary. We examined the development in symptom trajectories for breast cancer patients with low distress before surgery and explored potential risk factors for developing burdensome symptoms at a later point in time.